Multivacuolated mucin-filled cells: a unique cell characteristic of plexiform neurofibroma. A report of 11 cases - Michal, Michael; Kazakov, Dmitry V; Hadravský, Ladislav; Michalová, Květoslava; Rychlý, Boris; Michal, Michal (Human pathology, 2017)
The authors present 11 cases of plexiform neurofibroma (PN) that featured a very characteristic type of cell appearing as multivacuolated mucin-filled cells (MMFC). The 11 cases were obtained after reviewing 109 cases of PN. Six out of 10 patients showed clinical features of neurofibromatosis type 1. The size of PN ranged from 0.8 cm to 11.5 cm in the largest dimension. The lesions represented classical PN in all cases with myxoid, hypocellular stroma. The MMFC were found within the most myxoid tumorous nodules and were haphazardly located, typically featuring a variably sized, multivacuolated cytoplasm divided by fine septa with a small polygonal nucleus on one side, which was often compressed or slightly indented by the cytoplasmic mucous substances. In many cases, the cells resembled a soccer ball or a jellyfish. In all tested cases (n = 9), the MMFC stained for CD34; six cases were also positive with GLUT-1 antibody, and two cases expressed Claudin-1, whereas S-100 protein was negative. For comparison, we have reviewed a series of randomly selected non-PN, malignant peripheral nerve sheath tumors (MPNST) and of cases featuring non-neoplastic nerve trunks in our files, in which no MMFC were encountered. MMFC seem to be unique to myxoid areas of PN, where they occur in about 10% of cases. Their exact histogenesis is unclear but they might represent an intermediate type of cell between perineurial cells and fibroblasts. The awareness of this cell type in PN is especially important in limited (small) biopsy specimens where their recognition may provide a clue for the correct diagnosis.
Keywords: dospělí; Female; Vacuoles; dítě; vakuoly; Plexiform neurofibroma; Adult; Neurofibromatosis 1; ženské pohlaví; mladý dospělý; biopsie; Antigens, CD34; Glucose Transporter Type 1; Predictive Value of Tests; Adolescent; antigeny CD34; prediktivní hodnota testů; Soft tissue; Immunohistochemistry; lidé; Perineurial cells; Mucins; claudin-1; Multivacuolated mucin-filled cells; imunohistochemie; prognóza; Claudin-1; muciny; Male; Neurofibroma, Plexiform; nádorové biomarkery; Aged; neurofibromatóza 1; Biopsy; Multivacuolated lipoblast- like cells; Young Adult; Prognosis; Biomarkers, Tumor; Child; senioři; mužské pohlaví; přenašeč glukosy typ 1; plexiformní neurofibrom; mladiství; Humans